Maldives : Technical Assistance Report-Reform Options to Strengthen Tax Policy. (IMF Staff Country Reports; Country Report ;, 2019)
This report reviews tax policy in the Maldives and identifies reform options to support efficiency, equity, and revenue. The absence of a broad-based personal income tax (PIT) generates revenue leakages and significantly diminishes the role of tax policy in income redistribution. A modern tax design requires a holistic view of the taxation of different sources of income and different legal forms of taxpayers to maintain tax neutrality, to the extent possible, while preserving some degrees of progressivity, simplicity, and administrability. Moreover, updating the tax system to cope with recent international developments is vital to safeguard revenues. While strengthening the goods and services tax (GST) can raise revenues in the short- to medium-term, a property tax is an important option for the long-term. The diagram below demonstrates reform priorities, as identified in this report, to modernize tax policy in the Maldives.